Toxicological Impacts of Pesticides and Heavy Metals on Amazon Fish: Trends and Future Perspectives - Braz-Mota, Susana; Val, Adalberto Luis; Duarte, Rafael Mendonça [UNESP] (Springer Nature, 2024)
The Amazon region has faced substantial anthropogenic pressures, resulting in an increase in the presence of pesticides and heavy metals in aquatic ecosystems. This situation is primarily attributed to population growth, uncontrolled urban expansion, high deforestation rates, and the expansion of mining activities. This 2024 describing different effects of metals (Cu, Hg, Mn, Cd, Pb, and Ni) and the Amazon basin. This chapter delves into the critical issue of pesticide and heavy metal pollution in Amazon’s aquatic environments, focusing on the toxi-cological effects and their implications for Amazonian fish populations. We also examine the varying degrees of toxicological vulnerability among different Amazon fish species based on recent studies. Furthermore, we offer insights into the prospects of the Amazonian aquatic biota within the context of this pollution and present emerging trends and prospective developments.
Keywords: Biomarkers; Contamination; Freshwater pollution; Lethal concentration; Physiology